Resolve Ties Method for Re-establishing Fit for Purpose Survey Boundaries - Ismail Wadembere (African Journal on Land Policy and Geospatial Sciences)
Countries including Uganda adopted Fit-for-Purpose (FFP) Land Administration as a viable approach towards achieving full coverage of land registration aimed at empowering communities to secure land rights and enhance land management. While FFP survey approaches have successfully achieved huge coverage in a reasonable time and at an affordable cost in some districts of Uganda and many other countries including Rwanda, Ghana, Ethiopia, and Indonesia; most reported land disputes on un-titled land which is the target for FFP approach are primarily due to boundaries conflicts. However, there is limited knowledge and no standard method for re-establishing boundaries for land parcels initially surveyed using FFP methods. In this paper, we evaluated different field land surveying procedures, approaches, and methods to come up with an optimal method for re-establishing FFP land boundaries.